2019
DOI: 10.5424/sjar/2019173-14357
|View full text |Cite
|
Sign up to set email alerts
|

Harvest chronological planning using a method based on satellite-derived vegetation indices and artificial neural networks

Abstract: Aim of study: Wheat appropriate harvest date (WAHD) is an important factor in farm monitoring and harvest campaign schedule. Satellite remote sensing provides the possibility of continuous monitoring of large areas. In this study, we aimed to investigate the strength of vegetation indices (VIs) derived from Landsat-8 for generating the harvest schedule regional (HSR) map using Artificial Neural Network (ANN), a robust prediction tool in the agriculture sector.Area of study: Qorveh plain, Iran.Material and meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Orbital images are commonly used in agriculture to identify spectral variations resulting from soil and crop characteristics at a large-scale, supporting diagnostics for agronomical crop parameters and helping farmers to make better management decisions. For example, over the years, orbital images were used to delimit management zones for annual crops [1], monitor within-field yield variability for many crops such as corn [2] and cotton [3], map vineyard variability [4], plan the wheat harvest [5], develop crop growth model [6], and map grasslands biomass [7,8], among others. Some of the main limitations related to orbital images are the lack of ground truth data (calibration) and the measurement accuracy of the agronomical variables [9].…”
Section: Introductionmentioning
confidence: 99%
“…Orbital images are commonly used in agriculture to identify spectral variations resulting from soil and crop characteristics at a large-scale, supporting diagnostics for agronomical crop parameters and helping farmers to make better management decisions. For example, over the years, orbital images were used to delimit management zones for annual crops [1], monitor within-field yield variability for many crops such as corn [2] and cotton [3], map vineyard variability [4], plan the wheat harvest [5], develop crop growth model [6], and map grasslands biomass [7,8], among others. Some of the main limitations related to orbital images are the lack of ground truth data (calibration) and the measurement accuracy of the agronomical variables [9].…”
Section: Introductionmentioning
confidence: 99%
“…Remote sensing, which concentrates on the images examination of the earth's surface, has quickly evolved since the discovery of the infrared spectrum in the early 1800s (Campbell, 2002). The application of remotely sensed images leads to collect of reliable and timely data from crop performance (Lyle et al, 2013, Taghizadeh et al, 2019. Most vegetation indexes (VIs) incorporate reflectance in a few wavebands, which could be collected mainly by satellite broadband sensors.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that Green Normalized Difference Vegetation Index (GNDVI) values were the most correlated with grain yield. The contributions of satellite imagery in agriculture are also related to the classification of agricultural surfaces (SONOBE et al, 2018), land use , spatial predictions of soil properties (SILVERO et al, 2021;SICRE et al, 2020), quantification of the available pasture biomass (REIS et al, 2020), to delimit management zones for annual crops (DAMIAN et al, 2020), monitor withinfield yield variability for many crops, such as corn and cotton , mapping vineyard variability and grasslands biomass (CISNEROS et al, 2020), plan the wheat harvest (TAGHIZADEH et al, 2019), develop crop growth model (LEVITAN and GROSS, 2018), among others.…”
Section: Satellite Imagery For Agriculturementioning
confidence: 99%